Measuring digital literacies: Junior high-school students' perceived competencies versus actual performance - Porat, Erez; Blau, Ina; Barak, Azy (Computers and education, 2018)
The widespread belief is that youth, "digital natives", who live their entire lives in media-rich digital environments and are ubiquitously connected through social networks, naturally develop digital competencies. This study investigated digital literacies among 280 junior-high-school students with the aim of comparing participants' perceived digital literacy competencies and their actual performance in relevant digital tasks. The findings showed that only a few of participants' perceived skills were related to their actual performance. Generally, participants displayed high confidence in their digital literacies and significantly over-estimated their actual competencies. This gap was most evident in social-emotional skills, which were, on average, perceived by students as their strongest skills, while their actual level of performance was very low. Positive strong correlations were found between participants' self-reported evaluations of different digital skills, indicating their perception as a single factor, while actual performance tests revealed low-to medium-size correlations between different literacies. For educational decision-makers, the findings highlight the importance of designing training programs aimed to develop students' digital literacies, with a special emphasis on social-emotional competencies. Such training may enhance important competencies needed, reduce unfounded self-perceptions, and thus, develop efficient digital functioning in contemporary society. •Previous studies mostly explored students' self-report digital literacies.•This study compares six perceived digital literacies with their actual performance.•Students (n = 280, age∼13) significantly over-estimated their digital competencies.•Perceived literacies were high to very-high, while performance was average-low.•This perception-performance gap was most evident in social-emotional literacies.